2010
DOI: 10.1074/jbc.m110.137190
|View full text |Cite
|
Sign up to set email alerts
|

Role of NEK6 in Tumor Promoter-induced Transformation in JB6 C141 Mouse Skin Epidermal Cells

Abstract: NEK6 (NIMA-related kinase 6) is a homologue of the Aspergillus nidulans protein NIMA (never in mitosis, gene A). We demonstrate that overexpression of NEK6 induces anchorageindependent transformation of JB6 Cl41 mouse epidermal cells. Tissue arrays and Western immunoblot analysis show that NEK6 is overexpressed in malignant tissues and several cancer cell lines. Our data also show that NEK6 interacts with STAT3, an oncogenic transcription factor, and phosphorylates STAT3 on Ser 727 , which is important for tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 26 publications
1
47
1
Order By: Relevance
“…The molecular mechanisms that underlie these observations are unknown, and could reflect a nonmitotic function of NEK6. For example, NEK6 might affect the transcriptional programme of a cancer cell through phosphorylation of STAT3 on Ser727, an event that is required for maximal transcriptional activity (Jeon et al, 2010). Although kinases are generally regarded as druggable, developing NEK6-selective compounds will be a challenge, because the active site is identical to that of NEK7.…”
Section: Box 2 Mitotic Kinases As Anti-cancer Targetsmentioning
confidence: 99%
“…The molecular mechanisms that underlie these observations are unknown, and could reflect a nonmitotic function of NEK6. For example, NEK6 might affect the transcriptional programme of a cancer cell through phosphorylation of STAT3 on Ser727, an event that is required for maximal transcriptional activity (Jeon et al, 2010). Although kinases are generally regarded as druggable, developing NEK6-selective compounds will be a challenge, because the active site is identical to that of NEK7.…”
Section: Box 2 Mitotic Kinases As Anti-cancer Targetsmentioning
confidence: 99%
“…The NEK6 interactome as shown in Table 3 includes many genes putatively involved in immune signaling including IKBKB, DDX3X, ILF2, PRDX4, RHOC, S100A8, S100A9, and TOLLIP; however, none of these proteins act as direct NEK6 substrates in vitro in comparison to the potent substrates CK1α and YES1 (Supplemental Figure 6). In addition, NEK6 has previously been reported to interact with RELB (Vaz Meirelles et al, 2010) and increase the activity of an NFκB promoter (Matsuda et al, 2003), and it has also been previously reported to phosphorylate STAT3 (Jeon et al, 2010); however, RELA, RELB, STAT1, STAT3, and STAT5 are also not phosphorylated to an appreciable extent by NEK6 in our in vitro kinase assay. Thus, the impact of NEK6 on immune signaling may be indirect or the relevant substrate(s) have yet to be identified.…”
Section: Gene Expression Changes Mediated By Nek6 Substratesmentioning
confidence: 48%
“…Subsequently, it was demonstrated that NEK6 could phosphorylate hydrophobic motifs of RPS6KB1 as well as SGK1 in vitro (Lizcano et al, 2002). In addition, STAT3 phosphorylation at serine 727 has been implicated in the 7 transformation activity of NEK6 previously (Jeon et al, 2010). However, inducible expression of NEK6 in LHSR-AR cells does not increase phosphorylation on RPS6KB1 at Thr412 or STAT3 at Ser727 with or without growth factor stimulation as compared to cells expressing kinase-dead NEK6 or GFP (Supplemental Figure 3B).…”
Section: Introductionmentioning
confidence: 96%
“…The enhanced expression of Nek6 has been demonstrated in cancer cell lines, tissue samples from human cancer patients, and in vivo animal models. 10,[12][13][14]19 Specifically, Nassirpour, et al and Jeon et al recently demonstrated that Nek6 overexpression stimulates cell transformation and tumor growth in a mouse model. 14,19 These results indicate that Nek6 overexpression plays an important role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%